Dal Convegno “Una legge costituzionale per Roma Capitale” (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
The present study deals with an essential issue for the city of Rome, but a very difficult objective to achieve: a constitutional law for Roma Capitale. The text traces some events in the urban history of the capital, in continuity with the themes dealt with in the issue n. 14 of L’ADC: Rome, still Capital of Italy?